Minoan Crete : Bronze Age civilisation (1998)
[Dt.:] Die Seite stellt allgemeine Informationen zu den großen und einigen kleineren bronzezeitlichen Stätten Kretas zur Verfügung. Während die Beschreibungen meist eher knapp gehalten sind, findet man umfangreiches Fotomaterial zu Palästen, Siedlungen oder Gräbern. Eine Chronologie erleichtert die Orientierung. - [Engl.:] This site offers basic information about the major and minor archaeological sites of Crete. Though the descriptions are pretty short there are a lot of photographs of palaces, settlements or thombs. There is also a chronology for better orientation.